2004
DOI: 10.1093/jjco/hyh035
|View full text |Cite
|
Sign up to set email alerts
|

Hypermethylation-associated Inactivation of the SOCS-1 Gene, a JAK/STAT Inhibitor, in Human Pancreatic Cancers

Abstract: The results suggested that this gene is silenced in a substantial portion of pancreatic cancers through mechanisms that cause methylation in the promoter region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 13 publications
0
32
1
Order By: Relevance
“…For example, inactivation of the SOCS gene by methylation has been previously described in hepatocellular, pancreatic, lung, ovarian, and breast carcinomas (25,35,51,66,75). Since CpG island methylation generally results in complete absence of transcription, and increased baseline SOCS1 synthesis was observed in RC3 relative to WT8 cells (see Fig.…”
Section: Discussionmentioning
confidence: 76%
“…For example, inactivation of the SOCS gene by methylation has been previously described in hepatocellular, pancreatic, lung, ovarian, and breast carcinomas (25,35,51,66,75). Since CpG island methylation generally results in complete absence of transcription, and increased baseline SOCS1 synthesis was observed in RC3 relative to WT8 cells (see Fig.…”
Section: Discussionmentioning
confidence: 76%
“…Because loss of expression of SOCS molecules has been reported in several human malignancies (18)(19)(20)(21)(22), we tested whether this could be the case of thyroid tumors, whose cytokine pathways were previously shown constitutively activated. For such purpose, purified epithelial cells from 10 PTC, 10 FTC, and 5 UTC, previously examined for positivity to IL-4 and IL-10 (data not shown), were analyzed by Real-Time PCR analysis for mRNA expression of SOCS1, SOCS3, and SOCS5, potent inhibitors of JAK/STAT activation.…”
Section: Resultsmentioning
confidence: 99%
“…The recent research data also showed that SOCS-1 negatively regulated the response of chronic hepatitis C (CHC) to a-interferon (IFN-α) [12,13] . Methylation of SOCS-1 is implicated to be correlated with carcinoma, including hepatocarcinoma, pancreatic cancer, multiple myeloma and myeloid leukemia [14][15][16][17][18][19] . Expression of SOCS-1 was regulated by many factors.…”
Section: Introductionmentioning
confidence: 99%